2011
DOI: 10.1017/s0144686x10001285
|View full text |Cite
|
Sign up to set email alerts
|

Time spent in bed at night by care-home residents: choice or compromise?

Abstract: This paper examines the amount of time that care-home residents spend in bed at night, focusing on how residents' bedtimes and getting-up times are managed. Using a mixedmethods approach, diary data were collected over 14 days from 125 residents in ten care homes in South East England. The findings indicate that residents spent, on average, nearly 11 hours in bed at night, significantly more time than was spent sleeping. There was greater variance in the amount of time residents who needed assistance spent in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 17 publications
4
39
0
Order By: Relevance
“…As well as the obvious issue of noise and light, many care homes use routine practices that involve staff entering the rooms of residents to check on them at regular intervals, sometimes hourly (Kerr et al, 2008;Luff et al, 2011;Eyers et al, 2012). In support of previous findings from Kerr et al (2008), both staff and residents in this study felt that these overnight checks significantly contributed to poorer sleep quality of residents.…”
Section: Check Calls On Residentssupporting
confidence: 78%
See 3 more Smart Citations
“…As well as the obvious issue of noise and light, many care homes use routine practices that involve staff entering the rooms of residents to check on them at regular intervals, sometimes hourly (Kerr et al, 2008;Luff et al, 2011;Eyers et al, 2012). In support of previous findings from Kerr et al (2008), both staff and residents in this study felt that these overnight checks significantly contributed to poorer sleep quality of residents.…”
Section: Check Calls On Residentssupporting
confidence: 78%
“…However, as discussed in Luff et al (2011), it was found that the capacity of residents to exercise control over their sleep environment correlated with physical and cognitive impairment, with those most disabled experiencing the least control over their sleep environment. As such it is important to remember that those more frail and cognitively impaired will require even more proactive engagement from staff around their sleep.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Good night time sleep enhances cognitive and physical abilities, reduces the risk of falls, and also enhances quality of life (Livingston et al 1993;Leger 1994;Ersser et al 1999;Busto et al 2001;Martin 2002;Stepanski et al 2003). For older adults these are particularly important aspects of everyday life (Luff et al 2011;. However, studies undertaken in both North America and the United Kingdom indicate that the care home environment is not conducive to sleep (Alessi and Schnelle 2000;Kerr et al 2008).…”
Section: Older People's Perspectivementioning
confidence: 99%